Antiproliferative Effect of Electric Fields on Breast Tumor Cells In Vitro and In Vivo - Firman Alamsyah; Izzatun Niswah Ajrina; Fitriya Nur Annisa Dewi; Diah Iskandriati; Silvia Arin Prabandari; Warsito P. Taruno (Indonesian Journal of Cancer Chemoprevention, 2015)
Our research focused on the antiproliferative effect of low intensity (18 Vpp) and intermediate frequency (100 KHz) electrostatic wave between two capacitive electrodes on breast tumor cells in vitro and in vivo. In vitro study has been conducted by using MCF-7 cell lines treated with external electrostatic for 24, 48, and 72 hours of treatment and the cells number were calculated during treatment by using hemocytometer and presented as Growth Inhibition (GI)% efficacy. For in vivo, we used female mice (Mus musculus) strain C3H as animal model. The mice were injected with either MCF-7 cells, mammary tumor cells from C3H donor, or NaCl 0.9% (placebo) subcutaneously into the axilla area and exposed by external electrostatic in each cage for 12 hours in 2 weeks before necropsied. The adjacent and breast tissue were collected and stained with Hematoxylin – Eosin then analyzed for histopathological profile. In vitro study revealed the number of exposed cells decreased with lower proliferation rate than the non-exposed cells. Moreover, the external electrostatic caused 28-39% growth inhibition efficacy of MCF-7 cells. After 2 weeks of exposure, placebo mice were physically normal, whereas the tumor undergone significant shrinkage of more than 67% in size. Histopathological analysis of the mammary glands indicated infiltration of macrophages into the tumor area through the blood vessel. No abnormality was found in the skin layer and mammary glands of the breast tissue of placebo mice. Here, we present new knowledge of electro-capacitive cancer therapy (ECCT) as a novel treatment modality.Keywords : ECCT, tumor, in vitro, in vivo, breast cancer cells, antiproliferative